Child Sleep and Socioeconomic Context in the Development of Cognitive Abilities in Early Childhood - Hoyniak, Caroline P. (Child Dev, 2018)
Despite a robust literature examining the association between sleep problems and cognitive abilities in childhood, little is known about this association in toddlerhood, a period of rapid cognitive development. The present study examined the association between various sleep problems, using actigraphy, and performance on a standardized test of cognitive abilities, longitudinally across three ages (30, 36, and 42 months) in a large sample of toddlers (N = 493). Results revealed a between-subject effect in which the children who had more delayed sleep schedules on average also showed poorer cognitive abilities on average but did not support a within-subjects effect. Results also showed that delayed sleep explains part of the association between family socioeconomic context and child cognitive abilities.